Multinational teams in european and emerican companies (2008)
Incorporating team context into research and practice concerning team effectiveness in multinational organizations still remains an ongoing challenge. The purpose of this dissertation is to explore the influence of industry, corporate culture, structure, strategy and task characteristics on MNTs in business organisations and to develop a more comprehensive framework connecting the internal dynamics with contextual aspects of MNTs functioning in companies in Europe and the USA The study has been conducted in an Austrian (VA TECH), a German (Henkel) and an American company (K&M International). Forty-two problem-centred interviews have been conducted with 22 team members and 20 team leaders. Levels of uncertainty, stress and turbulence influence organisations and MNTs since teams and organisations have to reshape their strategies. Multinational strategy has a positive impact on MNTs while companies with a global strategy assign low value to diversity. MNT norms in companies with a strong corporate culture are reflective of the organizational culture. MNTs at companies with a weak corporate culture develop their own unique cultures and deviate from the values and norms set by the organization. Team composition, size and length of cooperation have a moderating effect on MNTs. We could identify several team leader competences that contribute to team success. The results show how teams reduce the complexity of operations by facilitating the creation and transfer of explicit and tacit knowledge and by transferring appropriate dimensions of the HQ corporate culture between geographically dispersed business units.